2014
DOI: 10.3390/e16094992
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio and Monte Carlo Approaches For the Magnetocaloric Effect in Co- and In-Doped Ni-Mn-Ga Heusler Alloys

Abstract: Abstract:The complex magnetic and structural properties of Co-doped Ni-Mn-Ga Heusler alloys have been investigated by using a combination of first-principles calculations and classical Monte Carlo simulations. We have restricted the investigations to systems with 0, 5 and 9 at% Co. Ab initio calculations show the presence of the ferrimagnetic order of austenite and martensite depending on the composition, where the excess Mn atoms on Ga sites show reversed spin configurations. Stable ferrimagnetic martensite i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 116 publications
3
31
0
Order By: Relevance
“…Therefore, when Ni (3d 8 4s 2 ) substitutes for Co (3d 7 4s 2 ), e/a increases. It is expected that the Curie temperature will decrease because of the weak ferromagnetic nature of Ni as compared with Co [36,37]. It seems that T C is sensitive to Ni addition; however, no direct relationship between T C and Co additions or the valence electron concentration e/a can be established.…”
Section: Magnetizationmentioning
confidence: 99%
“…Therefore, when Ni (3d 8 4s 2 ) substitutes for Co (3d 7 4s 2 ), e/a increases. It is expected that the Curie temperature will decrease because of the weak ferromagnetic nature of Ni as compared with Co [36,37]. It seems that T C is sensitive to Ni addition; however, no direct relationship between T C and Co additions or the valence electron concentration e/a can be established.…”
Section: Magnetizationmentioning
confidence: 99%
“…37 The transformation intervals into martensite for the substrate-constrained and the freestanding film are both very small and exhibit a two-stage process: first, an abrupt drop and then a gradual decrease of magnetization until a steady magnetization is reached below M F . When heating up again and passing the austenitic start temperature A S , the sample starts to transform back into austenite.…”
Section: B Transformation Temperatures In Freestanding and Constrainmentioning
confidence: 99%
“…For the forward transformation, a magnetic field makes the growth process more difficult since the martensite exhibits a substantial magnetocrystalline anisotropy. 37,54 As Zeeman energy is a volume contribution to free energy and not depending on interfaces, which affect nucleation, a magnetic field influences the growth process. Each nucleus consists of variants with different orientations.…”
Section: B Microstructural Origin Of Hysteresis Asymmetry and Field mentioning
confidence: 99%
“…On the other hand, recently we have done ab initio equilibrium energy calculations with tetragonal distortion c a / using 16-atom supercell Calculations have been carried out for two spin configurations referred to as "ferro" (i.e., all spins are parallel) and "ferri" (the spin of Mn Z on the Ga-lattice is reversed). It has been found that the "ferri" solution is energetically favorable for both alloys [16,29]. Therefore, we can propose that any small influences from defects, impurities or addition of magnetic atoms (for example, Co, Cr etc.)…”
Section: Origin Of Metamagnetic Behaviormentioning
confidence: 97%
“…To accomplish this, the three-dimensional lattice with real unit cell was divided into domains with random initial spin configurations. The intra-domain (intra-cluster) as well as inter-domain (inter-cluster) interactions are realized with the probability containing stochastic competition between the magnetic anisotropy field and the external magnetic field [17,29,33,34]. With respect to Co-doped Ni-Mn-Sn compound, in this paper we discuss magnetocaloric properties of Ni 45 Co 5 Mn 39 Sn 11 .…”
Section: Computation Of Magnetocaloric Effectsmentioning
confidence: 99%